Acute Alcohol Co‐Ingestion and Hospital‐Treated Deliberate Self‐Poisoning: Is There an Effect on Subsequent Self‐Harm?. Issue 1 (2nd March 2018) - Borruso, Luca D.; Buckley, Nicholas A.; Kirby, Katharine A.; Carter, Gregory; Pilgrim, Jennifer L.; Chitty, Kate M.
Abstract : The aim of this study was to determine the relationship between alcohol co‐ingestion in an index deliberate self‐poisoning (DSP) episode with repeated DSP and subsequent suicide. A retrospective cohort study was conducted involving 5, 669 consecutive index presentations to a toxicology service following DSP between January 1, 1996, and October 31, 2010. Records were probabilistically matched to National Coronial Information System data to identify subsequent suicide. Index DSPs were categorized on co‐ingestion of alcohol, and primary outcomes analyzed were repetition of any DSP, rates of repeated DSP, time to first repeat DSP, and subsequent suicide. Co‐ingestion of alcohol occurred in 35.9% of index admissions. There was no difference between those who co‐ingested alcohol (ALC+) and those who did not co‐ingest alcohol (ALC−) in terms of proportion of repeat DSP, number of DSP events, or time to first repeat DSP event. Forty‐one (1.0%) cases were probabilistically matched to a suicide death; there was no difference in the proportion of suicide between ALC+ and ALC− at 1 or 3 years. There was no significant relationship between the co‐ingestion of alcohol in an index DSP and subsequent repeated DSP or suicide. Clinically, this highlights the importance of mental health assessment of patients that present after DSP, irrespective of alcohol co‐ingestion at the time of event.